Analisis Sentimen Terhadap Bakal Capres RI 2024 di Twitter Menggunakan Algoritma SVM - Arfina Handayani; Ilka Zufria (Journal of Information System Research (JOSH), 2023)
In 2024, Indonesia will hold an election for head of state which will be the pinnacle of democracy in its political system. In the context of democracy, active community participation plays a key role in making general elections successful. However, there is still a tendency for people to only follow election procedures without actively participating. Therefore, this research was conducted to analyze public sentiment towards the 2024 presidential candidates, using data from social media Twitter. Social media, especially Twitter, has become the main platform for Indonesian people to express their political opinions, views and preferences. With the number of social media users reaching 170 million in 2021, Indonesia has great potential to gather various opinions and sentiments regarding general elections. This research aims to analyze sentiment using the Support Vector Machine (SVM) method on tweets containing hashtags related to three presidential candidates, namely Aniesbaswedan, Ganjarpranowo, and Prabowosubianto. The results of sentiment analysis show that the SVM method can be used to analyze sentiment with an accuracy of around 78.3 % overall. This accuracy is influenced by factors such as the amount of data used and the composition of positive and negative data. The sentiment data analyzed came from 1719 tweets from Twitter users, with a distribution of around 597 data for Aniesbaswedan, 627 data for Ganjarpranowo, and 495 data for Prabowo Subianto. This research provides insight into how Indonesian people convey their sentiments regarding the 2024 presidential candidates via social media. . This sentiment analysis can be an important reference in understanding the public's political preferences ahead of the upcoming general election.